eWom, Trust, and Perceived Value Related to Repurchases in the e-commerce Sector of Department Stores - Blanco-Gamero, Carolina (2023)
With the exponential growth in e-commerce retail sales, a variable such as perceived value is essential to consider, to warrant a successful long-term online business. However, eWom and perceived value have not yet been deeply studied together with other variables such as trust and repurchase in e-commerce belonging to department stores. Consequently, this study aims to analyze the influence of perceived value, eWom and trust on repurchases in those e-commerces. The sample was 196 people that repurchased from department stores e-commerce in Lima, Peru. The results were analyzed on Smart Pls. The results established that trust influenced repurchase and that eWom conditioned the perceived value of e-commerce in department stores. Furthermore, the results identified relevant variables that department stores’ e-commerce areas should consider to improve consumer repurchase through their e-commerce.